Experience of coronary care in diabetes. Issue 6002 (17th January 1976) - Harrower, A D; Clarke, B F
Abstract : During 1968-1973, 94 patients with diabetes were admitted to a coronary care unit (CCU) on 99 occasions with proved myocardial infarction. Altogether 24 of them (25-5%) died, giving an overall mortality at the time of discharge of 24% for the total admissions. This was just significantly higher than the 19% mortality recorded among non-diabetics treated in the same period but was much lower than that among diabetics treated for myocardial infarction before the advent of CCUs. No definite correlation was found between the type of anti-diabetic treatment and either mortality or the incidence of primary ventricular fibrillation. Patients with "poor" control of the diabetes before admission showed a significantly higher mortality than those with "good" control, but there was no significant difference in mortality between those with previous good control and non-diabetics.